(untitled) (Scientific journal of the Fergana State University, 2022)
The results of the analysis of water extract allowed us to establish changes in the degree of salinization and the qualitative composition of water-soluble salts according to the profile of the studied soils in favor of options using mineralized water for irrigation. After a three-year influence of irrigation with irrigation and saline waters, the irrigated meadow soils remained in the group of medium-saline soils starting from the arable horizons, while the arable horizons remained slightly saline. At the same time, there is a sharp increase in the dense residue in the variant with the use of drainage water.